A Study of the Magnetic and Structural Properties of Ultrathin Fe/Ni(111)/W(110) Films - Johnston, Hamish (My University, 1997)
The structural and magnetic properties of ultrathin Fe/Ni(111)/W(110) films are investigated using LEED, two Auger electron spectroscopy techniques and magneto-optic Kerr magnetometry. A 2 ML Ni(111) buffer layer is used to grow fcc Fe(111) films to a thickness of 3 monolayers. The Ni substrate aIIows good wetting and lattice matching of the Fe without significant interfacial diffusion. Above 3ML a continuous structural transition from fcc to bcc is observed.
An electron energy analyser for use with a spin polarised low energy electron diffraction (SPLEED) electron spin analyser was designed and built. The energy analyser is used to study the growth mode and structure of ultrathin Fe/Ni(111)/W(110) films using angle resolved auger emission spectroscopy (ARAES). A method is developed to fit computer simulations to the ARAES data to determine the growth mode of ultrathin films.
Preliminary magnetic measurements of the fcc phase below 4 ML indicate that the Fe films are ferromagnetic with a magnetic moment perpendicular to the surface at coverages of 0.25 to 2.0 ML. At 2.5 ML a spin reorientation transition appears to occur and both perpendicular and in plane magnetic moments are observed. At 3.0 ML the magnetic moment is in the plane of the film.
Keywords: Physics; Physics